Astaxanthin prevents postovulatory oocyte aging by targeting TNFR2 and inhibiting the TNF signaling pathway - Xin Wen; Zhe Han; Qi Yang; Ke-Song Shi; Dui Sun; Xiao-Jie Zhang; Cheng-Guang Liang (BMC Biology)
Abstract Background MII oocytes undergo time-dependent aging after ovulation, which is closely associated with impaired fertilization potential, poor embryo quality, and an increased risk of miscarriage. The apoptosis of cumulus cells and their secretion of TNF-α are identified as the primary contributors to postovulatory oocyte aging. Results In this study, we demonstrated that astaxanthin supplementation in culture medium effectively prevents postovulatory oocyte aging and extends oocyte lifespan in vitro. Importantly, this protective effect does not operate through the inhibition of cumulus cell apoptosis or TNF-α release. Notably, astaxanthin selectively binds to TNFR2 in oocytes, thereby preventing TNFR2 from interacting with TNF-α and inhibiting the activation of the TNF signaling pathway within oocytes. Furthermore, oocytes cultured with astaxanthin exhibit enhanced potential for early embryonic development and significantly increased IVF-ET litter size compared to controls. Conclusions Our findings, based on a mouse model, provide valuable insights into the potential clinical application of astaxanthin in mitigating post-ovulatory oocyte aging.